Generalization of the clinical experience of usе a combined drug in the form of a cream for topical application in the complex therapy of patients with chronic dermatoses - N. V. Kungurov; M. M. Kokhan; Yu. V. Keniksfest; I. A. Kuklin; O. G. Rimar; Ya. V. Kascheeva; E. I. Stukova (Лечащий Врач)
The data of therapy and clinical and laboratory monitoring of 42 patients with chronic dermatoses accompanied by pyogenic infection and skin defects, including: 12 patients with atopic dermatitis, 14 patients with eczema, 7 patients with vesicular dermatoses (acantholytic, vulgar pemphigus, During dermatitis), as well as patients with ulcerative pyoderma, are summarized. The age of the patients was from 18 to 74 years; men – 22, women – 20. Simultaneously with standard systemic therapy the сombined drug in the form of a cream was used as the main external remedy. According to bacteriological studies, the etiological factors for the development of secondary pyoderma in most patients were S. aureus and fungi of the genus Candida and/or their combination. High resistance of S. aureus strains to benzylpenicillin (20.0%), oxacillin (14.0%) was recorded; whereas only 1 strain out of 30 (3.3%) was resistant to gentamicin. Monitoring of these groups of patients established regression of EASI indices, the severity index of pyogenic manifestations, the severity index of bullous dermatoses by more than 75.0% from the baseline in the period from 7 to 14 or 21 days of therapy, which corresponded to the clinical remission within the inpatient stage of treatment. The study confirms the high efficiency of the innovative domestic drug cream in the complex therapy of patients with chronic, recurrent dermatoses with secondary infectious complications.